Strengthening food security through alternative carbohydrates in the city-state of Singapore - Lin, Amy Hui-Mei; Gómez-Maqueo, Andrea (Frontiers in Sustainable Food Systems, 2023)
Strengthening food security, in places where land and natural resources are limited or no longer available, is challenging. This is especially true for the production of staple food carbohydrates. Unlike some alternative foods, such as cultured meats, producing food carbohydrates using conventional agri-food approaches requires many natural resources, which are not available in some regions such as Singapore. Therefore, we must develop new, sustainable methods to enhance the quantity and nutritional quality of foods rich in carbohydrates. In this article, we review current developments in food security in the city-state of Singapore and emphasize the essential role of food carbohydrates in the food security plan. We discuss technology developments (i.e., indoor vertical farming, urban farming) used to enhance crop quality and production. We also make a few recommendations such as exploring underutilized and unconventional crops that are resilient and nutrient-dense, identifying hidden resources in local ecosystems (i.e., revalorizing agri-food processing by-products), and producing alternative carbohydrates (i.e., microbial and synthetic carbohydrates). Experience and approaches developed in Singapore provide an example to other regions and may inspire creativity in securing food availability.